Wireless Network Quality Analysis at the Tanah Abang Sub-district Office, Pali Regency Using the Quality of Service (Qos) Method - Anisah Fitria Agustin; Dedi Haryanto; Apriansyah (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
In the era of rapid globalization and information technology development, government institutions are required to adopt reliable and efficient technological systems to support public services. The Tanah Abang District Office, Penukal Abab Lematang Ilir Regency, South Sumatra Province, is responsible for various administrative services such as issuing birth certificates, identity cards, and other official correspondence, all of which rely heavily on stable network performance. However, current conditions indicate frequent internet slowdowns caused by unmanaged bandwidth usage and an unknown number of active wireless users, resulting in decreased service efficiency, especially during large data transfers. This study aims to analyze the implementation of the Hierarchical Token Bucket (HTB) method as a bandwidth management solution to improve network performance. Network quality is evaluated using Quality of Service (QoS) parameters, including throughput, delay, jitter, and packet loss. Data collection and traffic monitoring were conducted using the Wireshark application to capture and analyze network performance in real time. The results of this study are expected to provide insights into improving network stability and service effectiveness within government offices.